2020
DOI: 10.1007/s00467-019-04404-6
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutations in renal disease: an overview

Abstract: Kidneys have a high energy demand to facilitate the reabsorption of the glomerular filtrate. For this reason, renal cells have a high density of mitochondria. Mitochondrial cytopathies can be the result of a mutation in both mitochondrial and nuclear DNA. Mitochondrial dysfunction can lead to a variety of renal manifestations. Examples of tubular manifestations are renal Fanconi Syndrome, which is often found in patients diagnosed with Kearns-Sayre and Pearson's marrow-pancreas syndrome, and distal tubulopathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 94 publications
0
34
0
1
Order By: Relevance
“…The functional consequences of heteroplasmy depend on the degree of accumulation of the mutated mtDNA, the nature of the mutation, and the particular sensitivity of the affected cells for the mutational consequences. However, renal diseases caused by mutations of mitochondrial DNA were not the focus of this review and interested readers are referred to a recent review ( Govers et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The functional consequences of heteroplasmy depend on the degree of accumulation of the mutated mtDNA, the nature of the mutation, and the particular sensitivity of the affected cells for the mutational consequences. However, renal diseases caused by mutations of mitochondrial DNA were not the focus of this review and interested readers are referred to a recent review ( Govers et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] Excellent overviews of mitochondrial and nuclear gene mutations causing tubular defects are provided in various reviews. 8,20,[72][73][74] The most reported problem is a proximal tubular defect as proximal tubular cells are relatively J o u r n a l P r e -p r o o f vulnerable to oxidative stress. Most patients present with partial defects, including renal tubular acidosis (RTA), aminoaciduria, glycosuria, hypermagnesuria, or a combination of the above.…”
Section: Tubular Defectsmentioning
confidence: 99%
“… 10 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 Excellent overviews of mitochondrial and nuclear gene mutations causing tubular defects are provided in various reviews. 8 , 20 , 72 , 73 , 74 The most commonly reported problem is a proximal tubular defect, as proximal tubular cells are relatively vulnerable to oxidative stress. Most patients present with partial defects, including renal tubular acidosis (RTA), aminoaciduria, glycosuria, hypermagnesuria, or a combination of the above.…”
Section: Kidney Manifestations Of Genetic Mitochondrial Cytopathiesmentioning
confidence: 99%
“…Proximal tubular cells in renal tissue are rich in mitochondria and rely on oxidative phosphorylation for ATP generation [5]. Moreover, the importance of mitochondrial function in the kidneys is evident in inherited mitochondrial diseases with renal impairment [6]. Previously, it has been reported that the mitochondrial membrane potential in endothelial cells and podocytes of the kidneys is reduced by treating high-glucose in DN [7].…”
Section: Introductionmentioning
confidence: 99%